PENERAPAN STRATEGI MAKE A MATCH PADA MATERI AKHLAK TERPUJI TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS IV - Una, Ferlanda Ferlanda; Munirah, Munirah; Buhungo, Ruwiah A. (MIDA : Jurnal Pendidikan Dasar Islam, 2026)
This study aims to improve students’ learning outcomes on the material of commendable morals in class IV MI Al-Falah Limboto Barat. The type of research conducted by the researcher is classroom action research. The subjects of this study were 16 students of class IV MI Al-Falah Limboto Barat. Data collection techniques were observation, interviews, tests and documentation. Based on the results of the study, the application of the Make a Match learning strategy on the material of Commendable Morals in the subject of Aqidah Akhlak in class IV MI Al-Falah Limboto Barat has been proven to be effective in improving students’ learning outcomes, as seen from the increase in learning completeness from pre-cycle 56.25% to 68.75% in cycle I and reaching 87.5% in cycle II with 14 out of 16 students meeting the KKM 75. This strategy also succeeded in increasing student activity, motivation, and involvement in the learning process through a fun interactive atmosphere, where students enthusiastically searched for question-answer card pairs, discussed, and presented the results of group work, thus facilitating the internalization of commendable moral values. Overall, Make a Match as a cooperative model has proven to be a superior alternative for teachers to improve the quality of learning gradually through the cycle of planning, action, observation, and reflection until achieving a minimum success indicator of 80% classical completeness.